Carrier-envelope phase control over fragmentation of H2+ and D2. (August 2015) - Zohrabi, M; Berry, B; Kling, Nora G; Jochim, Bethany; Severt, T; Ablikim, U; Betsch, K J; Zeng, S; Anis, F; Wang, Z; Kübel, M; Kling, M F; et al.
Synopsis: We demonstrate control over fragmentation of H2 + and D2 molecules via the carrier-envelope phase of sub-5 fs laser pulses. Moreover, we attribute our findings to interferences between different pathways involving different net numbers of photons, revealing "high-order" pathways and the importance of the bandwidth.